2020
DOI: 10.1016/j.diii.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast density assessment between human eye and automated software on digital and synthetic mammography: Impact on breast cancer risk

Abstract: To evaluate the agreement between automatic assessment software of breast density based on artificial intelligence (AI) and visual assessment by a senior and junior radiologist, as well as the impact on the assessment of breast cancer risk (BCR) risk at 5 years. Materials and methods: We retrospectively included 311 consecutive women (40-74 years) without a personal history of breast cancer referred who underwent routine mammography between January 1, 2019 and February 28, 2019. Mammographic breast density (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“… 25 It can be successfully assessed by AI algorithms with an excellent agreement and high intraclass correlation coefficient between the AI software and expert readers. 26 A hybrid DL model evaluated by Yala et al included mammographic breast density, age, weight, height, menarche age, menopausal status, detailed family history of breast and ovarian cancer, breast cancer gene (BRCA) mutation status, history of atypical hyperplasia, and history of lobular carcinoma in situ. The IBIS/TC and hybrid DL models showed an area under the curve (AUC) of 0.62 (95% confidence interval [CI]: 0.57-0.66), and 0.70 (95% CI: 0.66-0.75), respectively.…”
Section: Risk Stratificationmentioning
confidence: 99%
“… 25 It can be successfully assessed by AI algorithms with an excellent agreement and high intraclass correlation coefficient between the AI software and expert readers. 26 A hybrid DL model evaluated by Yala et al included mammographic breast density, age, weight, height, menarche age, menopausal status, detailed family history of breast and ovarian cancer, breast cancer gene (BRCA) mutation status, history of atypical hyperplasia, and history of lobular carcinoma in situ. The IBIS/TC and hybrid DL models showed an area under the curve (AUC) of 0.62 (95% confidence interval [CI]: 0.57-0.66), and 0.70 (95% CI: 0.66-0.75), respectively.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Several guidelines already recommend supplemental imaging or chemo-prevention based on risk assessments [29,31,32] and recent results from the DENSE trial [33] have shown that a breast density based screening strategy could significantly reduce interval cancers compared to current screening. Our work is most closely related to the MyPeBS trial [34], which prospectively compares a personalized screening followup strategy based either Tyrer-Cuzick [8] or MammoRisk [35] risk assessments to current national recommendations. These studies point to substantial clinical interest in risk-based screening, however, current methods for devising screening policies rely on categorizing patients into a few coarse categories (e.g low and high risk), limiting personalization.…”
Section: Discussionmentioning
confidence: 99%
“…Still, some misclassification of MBD could have affected our results since we used visual classification using BI RADS by two experienced radiologists. However, a study reported very good agreement between automatic assessment software of breast density based on artificial intelligence (AI) and visual assessment by a senior and a junior radiologist [ 51 ]. The strengths of the study are a good quality of data collection by medical doctors, and comprehensive assessment of all factors associated with MBD.…”
Section: Discussionmentioning
confidence: 99%